Beyond the helium buffer: 12C−2 rotational cooling in cold traps with H2 as a partner gas: interaction forces and quantum dynamics. (17th September 2021) - Mant, Barry; Franz, Jan; Wester, Roland; Gianturco, F. A.
Abstract : The scattering cross-sections and corresponding rate coefficients for rotationally inelastic collisions of 12 C 2 − ( 2 Σ g + ) with H 2 ( 1 Σ g + ) are presented over a broad range of cold-trap temperatures. They have been calculated using quantum scattering theory that employs a new ab initio potential energy surface. The rate coefficients for the inelastic processes in the anionic partner are used to model the thermalisation dynamics of 12 C 2 − using H 2 as a buffer gas, a trap partner which is found here to be far more efficient than the typical buffer gas He and even more so than when using Ar as a partner gas. The microscopic physics underlying these findings is discussed in some detail. We additionally compute and discuss 12 C 2 − quadrupole transitions by spontaneous emission and use the newly computed rates to show that the anion's rotational levels should be in local thermal equilibrium at typical interstellar conditions. GRAPHICAL ABSTRACT: UF0001